Implementasi Model Pembelajaran Discovery Learning Terhadap Keaktifan Belajar Siswa Pada Mata Pelajaran PAI - Irnajuliana; Wardana; Aminullah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the implementation of the Discovery Learning model in Islamic Religious Education (PAI) at SMAN 23 Bone and its impact on student engagement. Islamic Religious Education plays a fundamental role in shaping students' character to be faithful, pious, and morally noble in accordance with national education goals. Student engagement in learning is an important indicator of educational process success that involves not only cognitive aspects, but also emotional and spiritual dimensions. This research employs a descriptive qualitative method with pedagogical, Islamic education, and psychological approaches. Data collection techniques were conducted through observation, interviews, and documentation with research subjects consisting of PAI teachers and tenth-grade students. Data validity was tested using triangulation of sources, methods, and time. The research findings indicate that Discovery Learning implementation is carried out through six stages: providing stimulation, problem identification, data collection, data processing, verification, and drawing conclusions. This model effectively enhances student engagement reflected through active participation, courage in expressing opinions, and independence in seeking information. Supporting factors include teacher competency, student enthusiasm, and adequate facilities and infrastructure, while inhibiting factors are limited time allocation and diverse student abilities